From Alarmed to Dismissive of Climate Change: A Single Item Assessment of Individual Differences in Concern and Issue Involvement. Issue 4 (4th July 2017) - Swim, Janet K.; Geiger, Nathaniel
ABSTRACT: The present paper tests the validity of using a single-item individual difference measure of climate change concern derived from the "Six Americas" project's descriptions of the US public's concern about climate change. The "Six Americas" project identified six segments of the US population proposed to range from the most (i.e. Alarmed) to least Concerned (i.e. Dismissive). The order is also proposed to relate to issue involvement with those in the middle of the continuum least involved. Three studies support the reliability, construct validity, and predictive validity of self-categorization into the six segments as a single-item individual difference measure of climate change concern. Results support both a linear relation with concern about climate change and a curvilinear relation with issue involvement. These findings suggest that the single-item self-categorization measure developed for use in this manuscript is a valid and concise measure for researchers to assess participants' opinions about climate change.